Ophthalmology in Extreme Environments - Subramanian, Prem S. (Springer International Publishing : Imprint: Springer, 2017)
Aiming to stimulate future research in ocular disorders that occur in specific environments presenting unique hazards to the eye, systemic health, or both, this book assists in identification and effective treatment for these cases. Ophthalmology in Extreme Environments identifies common approaches to the care of disease and injury in these conditions, recognizing gaps in knowledge and working toward better informing the reader. Topics covered include high altitude and vision changes, night vision and military operations, undersea environmental medicine, and modern eye trauma surgery and outcomes.
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books